2022
DOI: 10.3390/biom12111656
|View full text |Cite
|
Sign up to set email alerts
|

A PQS-Cleaving Quorum Quenching Enzyme Targets Extracellular Membrane Vesicles of Pseudomonas aeruginosa

Abstract: The opportunistic pathogen Pseudomonas aeruginosa uses quorum sensing to control its virulence. One of its major signal molecules, the Pseudomonas quinolone signal PQS, has high affinity to membranes and is known to be trafficked mainly via outer membrane vesicles (OMVs). We previously reported that several 3-hydroxy-4(1H)-quinolone 2,4-dioxygenases (HQDs) catalyze the cleavage of PQS and thus act as quorum quenching enzymes. Further analysis showed that, in contrast to other HQDs, the activity of HQD from Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…45 Recent studies have shown that Pseudomonas quinolone signal (PQS) is closely related to OMVs. 50 PQS also induced substantial release of MVs in all strains. 51 These OMVs can interact with other cells and release PQS into the surrounding environment.…”
Section: Bacterial Metabolites and Other Moleculesmentioning
confidence: 86%
See 1 more Smart Citation
“…45 Recent studies have shown that Pseudomonas quinolone signal (PQS) is closely related to OMVs. 50 PQS also induced substantial release of MVs in all strains. 51 These OMVs can interact with other cells and release PQS into the surrounding environment.…”
Section: Bacterial Metabolites and Other Moleculesmentioning
confidence: 86%
“…Recent studies have shown that Pseudomonas quinolone signal (PQS) is closely related to OMVs 50 . PQS also induced substantial release of MVs in all strains 51 .…”
Section: Components and Functions Of Bevsmentioning
confidence: 99%
“…When cell density is high, the accumulation of the signal in the extracellular medium allows the activation of a cellular response [1][2]. This system regulates various functions that require the concerted action of numerous cells such as bioluminescence, production of secondary metabolites, sporulation, biofilm formation, antibiotic resistance, and production of multiple virulence factors [3]. QS signal molecules are chemically diverse and characterized by having a low molecular weight [4].…”
Section: Introductionmentioning
confidence: 99%